A New Rationale for Implying Private Rights of Action and Section 7 of the Securities Exchange Act of 1934 (Washington University Law Quarterly, 1975)
In 1974, two Circuit Courts of Appeals refined a technique used to imply a private right of action on behalf of plaintiffs who were without express statutory remedies. The 1974 cases could eliminate much of the confusion under section 7 because they provide the means to explore fully the statutory and policy implications of a private right of action. This Article will examine the traditional private right rationales, the 1974 cases, the operation of the credit provisions, and the application of the recent developments to section 7.
Keywords: Actions and defenses; Credit